Uma análise do processo de constituição do professor leitor: os sentidos e significados produzidos - Ramalho, Mara Lúcia (2006)
The objective of the present research is to analyze, based on teachers talking, the meaning and significance produced by them about reading practices. Reading practices can be considered as the reading action, which implies not just the decodification of written language signals, but also the attribution of meaning and significance to the facts that are being presented. This concept makes it possible to understand reading as a process that surpasses the mere decoding of written texts. In view of the considered objective, field research was chosen as the methodology, whose referential theoretic methodology is based on socio-historical psychology. Information was gathered using semi-structured and recurrent interviews as well as life history narrative. Two teachers were chosen as subjects who were participants in the Normal Undergraduate Course Veredas. Three interviews were conducted with each of them (a life story narrative and two semi-structured interviews). The final considerations of the research point to the need to magnify the concepts of practical reading and reading; for the constitution of a vision over the preparation process of educators that contemplates the diverse reading practices; for the importance of the participation of not only the school in the preparation of readers, but also the family and the community. The study also points out that the analyzed subjects in the Normal Undergraduate Course-Veredas participation alone did not modify their sense of meaning regarding the act of reading